Amalgamation and local finance - Wright, Glen (Central European Public Administration Review, 2022)
Purpose: The article aims to measure the impact of the voluntary amalgamation approach applied in Ukraine in the course of the decentralization reforms undertaken over a period of five years, and assess how much these reforms have been successful in improving the local government fiscal situation. Ukraine began a long-delayed decentralization process in 2015 through amalgamation based on a voluntary approach, with an emphasis on improving the fiscal resources of the amalgamated units. The decentralization reform was based on three pillars: (1) voluntary amalgamation of the territorial units, (2) enhanced financial resources through own source revenues and infrastructure grants, and (3) utilization of inter-municipal cooperation to support improved service delivery. Methodology: A time series of fiscal data from amalgamated territorial communities in selected regions of Ukraine have been analysed to measure the impact of the amalgamation policy on the amalgamated territorial units. Findings: The fiscal improvements anticipated by the amalgamated territorial units have not been demonstrated by the statistical data analysis and no significant improvement in local government finances appears to have been realized through the application of a voluntary merging approach. There have been significant regional and urban/rural variations based on the population segments and access to financial resources. Academic contribution to the field: While there has been considerable research on the impact of merging or amalgamating local governments, there has been very little, if any, on the voluntary approach to amalgamation. The study seeks to address this problem and present evidence of the advantage of utilizing a voluntary over a mandatory approach to amalgamation. Significance: The study provides a unique opportunity to measure the impact of amalgamation process in Ukraine over a five-year period based on the voluntary approach to amalgamation and determine how much this approach and the accompanying policies have been successful in improving the local government fiscal situation.
Keywords: amalgamated territorial communities; fiscal decentralization; fiscal equalization; fiskalna decentralizacija; fiskalno izenačevanje; prostovoljno združevanje; voluntary amalgamation; združene teritorialne skupnosti